Binary And Ternary Complexes Of Β-Cyclodextrin With Isoniazid And Ethambutol: Characterization And Molecular Modeling Studies - Goh, Soen Qeng (2023)
Long term intake of antituberculosis drugs will lead to severe adverse reactions that will ultimately deteriorate a patient’s health and well-being. Presently, it is known that supramolecular macrocycles such as cyclodextrins (CDs) are useful to enhance drug solubility and targeting mechanism while reducing drug dosage by providing many therapeutic benefits. With that, the possibility of formation of drug-CDs ternary inclusion complex was explored, whereby β-cyclodextrin (β-CD) was chosen as the supramolecular host carrier to accommodate two kinds of first-line antituberculosis guest drug molecules simultaneously, namely isoniazid (INH) and ethambutol (ETB). The inclusion complex of β-CD/INH/ETB was prepared using solvent evaporation method. Fourier transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance spectroscopy (1H-NMR), and 2-dimensional nuclear Overhauser effect spectroscopy (2D-NOESY) NMR were used to investigate the functional groups and structure of the complex. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were employed to study the surface morphology and crystallinity changes during complex formation. Thermogravimetric analysis (TGA) was performed to investigate the thermal properties of the complex. FT-IR and both types of NMR results had revealed the successful penetration of both the drug molecules into the β- CD cavity. SEM images and XRD spectra had shown a drastic change in surface structure and reduction in crystallinity during complex formation, which had indicated successful formation of a new compound.